DAMPAK PAJAK TURIS TERHADAP PELESTARIAN LINGKUNGAN DESTINASI WISATA DI INDONESIA - Bagus Aldian; Mutia, Devina Kansa; Musfirah, Dhia Khalishah; Puriandini, Veronika (Politeknik Keuangan Negara STAN, 2025)
This article discusses the impact of tourist taxes on environmental conservation in tourist destinations in Indonesia. Tourism is an important sector in the economies of many countries, but increasing the number of tourists can cause environmental damage and damage local traditions. A tourist tax could be a potential solution by creating an additional source of funding for environmental conservation. The revenue from this tax could be allocated to nature conservation projects, environmental education programs, and efforts to preserve local cultural heritage. It can also engage tourists in their responsibility to preserve the destinations they enjoy. However, the implementation of a tourist tax also has negative impacts, such as increased prices in tourist destinations and a potential reduction in visitation. Therefore, the government needs to conduct in-depth research, engage the public, and implement effective administration and supervision to ensure the success of the tourist tax.